In vitro micropropagation of an endangered medicinal orchild (Anoectochilus setaceus Blume) through protocorm-like bodies - Hong Thuy, Tran Thi; Gam, Do Thi; Hung, Nguyen Khac; Ngoc, Pham Bich; Ha, Chu Hoang (Academia Journal of Biology, 2015)
Anoectochilus setaceus Blume is one of the rare medicinal orchids in Vietnam. Anoectochilus setaceus has various functions in traditional medicine, such as anti-tumor, lipase decreasing, anti-diabetes, anti-hepatitis... Nowadays, lan kim tuyen individuals in the nature is limited because of its slowly growth, special condition requirements and especially, been excessively exploited, that can result in the extinction. In order to preserve plant biodiversity, develop and expand lan kim tuyen cultivation, a rapid micropropagation protocol through PLBs-protocorm like bodies is established. Detached apical shoots were used as explants for PLBs initiation. After 30 days-culture, 86.25% of the explants regenerated to PLBs with fresh weight approximately 0.23 gram per clump. Shoots were quickly regenerated from the derived PLBs by transplanting onto shoot regenerating medium in next 30 days. Single intact shoot separated from shoot clump was transferred to elongating and rooting formation medium. After 120 days of culturing process, micropropagation productivity achieves about 29.66 plantlets per PLBs.